Diversity of Morphology and Reproduction Phenology of Clove Germplasm on Manipa Island, Western Seram, Maluku - Ulath, Yohana; Mahulette, Asri S; Raharjo, Simon H T (Universitas Pattimura, 2023)
Manipa Island, in Western Seram Regency, Maluku Province, Indonesia, is one of the cloves-producing centers in Maluku. So far, the study of clove germplasm on Manipa Island is still minimal, especially studies on morphological diversity and flowering phenology. The study aimed to (1) obtain data and information on morphological characteristics of various clove germplasm on Manipa Island and (2) obtain data and information on reproductive phenology of various clove germplasm on Manipa Island. The study was carried out in two clove distribution areas on Manipa Island, namely West Tomalehu Village (altitude >600 m asl) and East Tomalehu Village (<600 m asl), from March-December 2021. Morphological investigation in this study used survey methods, whereas observations of reproductive phenology were carried out through interviewing representative farmers. The results showed three types of cloves on Manipa Island, namely Tuni, Red Zanzibar, and White Zanzibar. Based on Hierarchical Cluster Analysis (HCA), cloves in Manipa Island were divided into two large groups with a coefficient of dissimilarity of 33%, namely the Tuni clove group as the first group and the Red Zanzibar and White Zanzibar cloves as the second group. The main characterizing character based on Principle Component Analysis (PCA) indicated that the characterizing character in the Red Zanzibar and White Zanzibar cloves was the color of the shoots. In contrast, in Tuni cloves, characterizing characters were the color of the old leaves and the color of petiole tips. The phenology of clove reproduction on Manipa Island consisted of 7 stages, namely: flower induction, flower initiation, pre-anthesis, anthesis, pollination and fertilization, as well as fruit and seed formation, fruit and seed enlargement, and fruit and seed ripening. The timing of the occurrence of each of these phenological stages throughout the year in Manipa Island was determined in this study.